Analisis Perceived Organizational Support, Quality Culture, dan Kepuasan Kerja sebagai Second-Order Factor terhadap Turnover Intention Karyawan Generasi Y di ATC (Air Traffic Control) - Honorata Ratnawati Dwi Putranti; Suparmi Suparmi; Sri Suprapti (Jurnal Maksipreneur, 2021)
The meeting between generations is now starting to be felt in all organizations, and new things in Human Resources management. Differences in character, motivation, and characteristics in each create a contribution to the human resource management of an organization/company. This study aims to analyze Y-generation employees at ATC (Air Traffic Control) by examining the relationship between variables, perceived organizational support, job satisfaction, quality culture, and intention to move. The research object is ATC employees of seven airports in Indonesia with a total population of 620. The sample of this study is Y-generation of the ATC employees, which is as many as 225, with a purposive sampling method. Research data processing using AMOS version 24 with job satisfaction as the second-order (internal and external dimensions). The results showed that perceived organizational support and quality culture affected turnover intention which was moderated by job satisfaction. This research is expected to contribute to the understanding of job satisfaction which consists of external and internal dimensions that affect Y-generation in turnover intention.